Examining adverse fetal/neonatal outcomes associated with severe maternal morbidity. (21st April 2020) - Lawton, Beverley; Filoche, Sara; MacDonald, Evelyn Jane; Stanley, James; Meeks, Maggie; Stone, Peter; Storey, Francesca; Geller, Stacie E.
Abstract: Background: While there is a global focus on severe maternal morbidity (SMM), less is known about the impact of SMM on fetal and neonatal outcomes. Aims: To examine fetal/neonatal outcomes associated with SMM. Materials and Methods: A national New Zealand (NZ) retrospective cohort study describing fetal/neonatal outcomes of all women with SMM admitted to a NZ Intensive Care Unit (ICU) or High Dependency Unit (HDU) in 2014. Adverse fetal/neonatal outcomes were defined as one or more of the following: fetal or early neonatal death, hypoxic ischaemic encephalopathy, Apgar score less than seven at five minutes, admission to Neonatal Intensive Care Unit or Special Care Baby Unit. Results: There were 400 women with SMM admitted to NZ ICU/HDU units in 2014, and 395 (98.8%) had complete birth/pregnancy outcome information. Of these, 49.4% (195/395) were associated with an adverse fetal/neonatal outcome. Indigenous Māori women had a 30% higher rate of adverse fetal/neonatal outcome compared to NZ European women (63.7% and 48.9% respectively; relative risk = 1.30, 95% CI 1.04–1.64). Pre‐eclampsia was associated with an adverse fetal/neonatal outcome in 67% (81/120). Perinatal‐related mortality rate was 53.1 per 1000 total births compared to NZ perinatal mortality of 11.2 per 1000 total births for 2014. Conclusion: SMM events are associated with high rates of adverse fetal/neonatal outcomes with a higher burden of adverse events for Māori. Further research is needed to explore opportunities in maternal and neonatal care pathways to improve fetal/neonatal outcomes and address inequities.